Comparative analysis of the performance of Unity and Unreal Engine game engines in 3D games - Abramowicz, Kamil; Borczuk, Przemysław (Journal of Computer Sciences Institute, 2024)
The article compared the performance of the Unity and Unreal Engine game engines based on tests conducted on two nearly identical games. The research focused on frames per second, CPU usage, RAM, and GPU memory. The results showed that Unity achieved a better average frame rate. Unreal Engine required more RAM and GPU resources. Analyzing CPU load values revealed that on the first system, Unity demanded less CPU usage. However, on the second system, Unreal Engine used over 10 percentage points less CPU. The conclusions from the research partially confirm the hypothesis that Unity requires fewer computer resources, although in some cases, Unreal Engine may demand fewer CPU resources.